SOFIA THE FIRST: WHAT MAKES A TEXT MAKE SENSE - Sutopo, Djoko (Language Circle: Journal of Language and Literature, 2014)
Based on the concern that in teachings, our teachers are not sure how to exploit texts, this study aims at describing what makes a text and what makes a text make sense. A literary work entitled Sofia the First has been the object of the study. The focus is on unlocking the text before analyzing its cohesiveness and its coherence. Reference and topic /comment of the text is also discussed before describing the advantages of using such literary text in teaching and learning process. The findings suggest that individual sentence has been a concern of traditional language teaching. However, it its natural state, language is not isolated sentences. Rather, it is the text that is the significant unit of language. As teachers of foreign language users, our top priority is to help learners understand and produce texts for different purposes in a variety of genres. Issues such as what makes a text and what makes a text make sense are significant to address.